Deblurring the concept of a breach of the peace as a component of contemporary international collective security. (2nd January 2019) - Friman, Johanna
ABSTRACT: Plausibly representing one of the most obscure concepts in the jus ad bellum, 'breach of the peace' may potentially serve as an essential component of contemporary international collective security. However, this potential may not be realised as long as its legal parameters remain obscure. The aim of the present article therefore is to conceptually and contextually shed some light on the outer legal boundaries of a 'breach of the peace'. The deblurring examination contemplates, first, the 'peace' that is breached, with the central focus thereafter directed towards a tridimensional examination of the conceptual construction of a 'breach' of the peace encompassing ratione temporis, ratione materiae and ratione personae perspectives. The examination is methodologically projected from a clarifying position, drawing on comparative elements from related international legal regimes, primarily international criminal law.